GAMBARAN TINGKAT PENGETAHUAN MASYARAAT TERHADAP PERILAKU PENGGUNAAN ANTIBIOTIK DI DESA GRUMBUL GEDE SELOMARTANI KALASAN - Syarifah, Nur Yeti (STIKES Wira Husada Yogyakarta, 2016)
Background: Antibiotics is a very well known drug and widely used by thecommunitiy, that can occure antibiotics abuse in society. The relatively increasinguse of antibiotics has appeared to raise a variety of problems and be a generalhealth threats particulery in terms of antibiotics resistance. The most action ofantibiotics abuse in society consist of student self-treatment without doctorprescription. One of the important things that affect a persons actions andbehavior is knowledgeObjective: This aim of study was to investigate the relationship between thelevels of knowledge about antibiotics with antibiotics use behavior in the grumbulgede village, Selomartani, Kalasan Sleman Methods: This research was carried out by using descriptive analytic methodsquantitative with cross sectional approach. The sampling technique used clusterrandom sampling with 46 respondents. The research instrument usedquestionnaires as well as data analysis and correlation Chi-Square. Results The result of Chi-Square test showed a significant correlation betweenthe level of knowledge about antibiotics and antibiotics usage without Theanalysis with gain value (p) 0002. because the value of (p)